A parametric study of neck moment response in a 3 year old child subjected to oblique side impact. - Shasthri, Sivaguru; Kausalyah, Venkatason; Shah, Qasim Hussain; MahmoudIdres, Moumen Mohamed; Wong, S. V. (Asian Research Publishing Network (ARPN), 2016)
The effect and interactions of various parameters on the Neck Moment experienced by a three year old child during side impact is investigated using a pre-validated numerical model. The simulation involves a HYBRID III 3-year old child Anthropometric Test Device (ATD) model restrained in a Child Restraint System. The numerical model assembly is comprised of a combination of both Finite Elements (FE) and Multi-body ellipsoids (Mb). It is subjected to lateral and oblique side impact crash using the Prescribed Structural Motion method. The model is adapted to investigate the effect of intrusion and oblique impacting angles. The Latin Hypercube Sampling (LHS) design is adopted for the Plan of Experiments in which six parameters are subjected to two different impact velocities. Statistical methods are employed in which both quantitative and qualitative parametric studies are carried out. The study indicates greater parametric significance at high impact speed and at wide impact angles (φ = 60°). The impact angle parameter is largely shown to be the most significant parameter in affecting the Neck Moment response. The impact angle parameter trend is found to be very similar for both impact speeds. A relatively safe region is found to exist between impact angles 45° and 65°. © 2006-2016 Asian Research Publishing Network (ARPN).